Inovação social para o envelhecimento ativo: iniciativas em Portugal e no município de São Carlos -SP - Mello, Kemilly Bianca de (2021)
The idea of social innovation (SI) stands out today, but when linked to active aging, there is a very large gap in knowledge and practice, especially in Brazil. In the face of this unexplored theme, this research aims to identify and analize SI initiatives focused on active aging in the city of São Carlos-SP and north region of Portugal. This research used a theoretical-empirical methodology and a multi-case study aimed at identifying SI initiatives linked to active aging and quality of life. In addition, a study of the state of the art of SI and active aging was carried out to understand and update itself on the productions developed. The project referring to this research was approved by the Research Ethics Committee - CEP / UFSCar (Opinion nº 3,350,844). The results and discussions point to the existence of well-consolidated SI initiatives for active aging in Portugal, mainly due to the support for this demand in the country and on the European continent. In São Carlos, the initiatives identified, despite not calling themselves SI, aim to meet the demands associated with aging in an innovative way. In addition, this study shows the relevance of research on the theme of social innovation for active aging in the Brazilian context, since there is a lack of knowledge on this theme and there are no public policies for social innovation in Brazil. The final considerations, on the other hand, present reflections and possibilities to expand this theme for its diffusion and incentive to social transformations.